Safety of Tattoos, Permanent Make-Up, and Medical Implants in Population-Based 3T Magnetic Resonance Brain Imaging: The Rhineland Study - Lohner, Valerie; Enkirch, Simon J.; Hattingen, Elke; Stöcker, Tony; Breteler, Monique M. B. (Frontiers in Neurology, 2022)
Excluding persons from magnetic resonance imaging (MRI) research studies based on their medical history or because they have tattoos, can create bias and compromise the validity and generalizability of study results. In the population-based Rhineland Study, we limited exclusion criteria for MRI and allowed participants with passive medical implants, tattoos or permanent make-up to undergo MRI. Thereby, we could include 16.6 % more people than would have been possible based on common recommendations. We observed no adverse events or artefacts. This supports that most passive medical implants, tattoos and permanent make-up are MRI suitable and can be scanned in research settings.